Disordered dislocation configuration in submicrometer Al crystal subjected to plane strain bending. (1st March 2016) - Hu, T.; Ma, K.; Topping, T.D.; Jiang, L.; Zhang, D.; Mukherjee, A.K.; Schoenung, J.M.; Lavernia, E.J.
Abstract: Bending tests of submicrometer Al pillars were performed in-situ in a transmission electron microscope (TEM). The Al crystal in the bent region experienced substantial lattice distortion, as well as grain refinement resulting in a disordered dislocation configuration arising from a random distribution of low angle grain boundaries (LAGBs). This observed disordered dislocation configuration is in contrast to formation of a low energy dislocation configuration, as predicted on the basis of the theory of strain gradient plasticity, for bulk materials subjected to plane strain bending. Graphical abstract: Bending tests of submicrometer Al pillars were performed in-situ in a transmission electron microscope (TEM). The unique findings are: 1) the Al crystal in the bent region experienced substantial lattice distortion, as well as grain refinement; 2) a disordered dislocation configuration arising from a random distribution of low angle grain boundaries (LAGBs). This observed disordered dislocation configuration is in contrast to the prediction on the basis of the theory of strain gradient plasticity, for bulk materials subjected to plane strain bending.